Structural Model of Mental Health Based on Job Stress: The Mediating Role of Job Satisfaction and the Moderating Role of Job Experience in Employees of Aghajari Oil and Gas Exploitation Company - Mohamad Najafpour; Marzieh Mashalpourfard (طب کار)
Introduction: Job stress is a psycho-physiological reaction that occurs when a person’s work skill do not align with their job expectations. Long-term exposure to job stress affects the mental wellbeing and overall health of the person. The aim of this study was to predict mental health considering job stress, while factoring in job satisfaction as a mediator and the influence of job history in employees of Aghajari Oil and Gas Exploitation Company. Materials and Methods: The present study was a descriptive-correlational one in (2023) in Omidieh City. The statistical population included all 800 employees working for Aghajari Oil and Gas Exploitation Company. Utilizing the Krejcie & Morgan table and the list of names, a sample of 260 individuals was drawn through simple random sampling. To collect information, the Goldberg General Health Questionnaire, the Hellrigal Job Stress Quesionnaire, the Minnesota Job Satisfaction Questionnaire, and the Job History Questionnaire were employed. Structural equation analysis was conducted utilizing SPSS-27 and AMOS-25 software for data analysis. Results: The results indicated that the presented model exhibited a good fit, and all direct and indirect relationships between job stress and mental health through job satisfaction in employees were significant. Furthermore, work experience influenced the relationship between job stress and job satisfaction, as well as the link between job satisfaction and mental health. Conclusion: Job stress directly affects mental health, while mediating factors such as job satisfaction and moderating factors such as job experience can strengthen or weaken these effects. Consequently, implementing work policies that take into account the factors examined in this research can improve employee well-being, especially in high-stress jobs.